2014
DOI: 10.1161/circep.113.001404
|View full text |Cite
|
Sign up to set email alerts
|

Noninducibility in Postinfarction Ventricular Tachycardia as an End Point for Ventricular Tachycardia Ablation and Its Effects on Outcomes

Abstract: Background-Although ventricular tachycardia (VT) ablation is a widely used therapy for patients with VT, the ideal end points for this procedure are not well defined. We performed a meta-analysis of the published literature to assess the predictive value of noninducibility of postinfarction VT for long-term outcomes after VT ablation. Methods and Results-We performed a systematic review of MEDLINE (1950MEDLINE ( -2013, EMBASE (1988EMBASE ( -2013, the Cochrane Controlled Trials Register (Fourth Quarter, 2012), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
74
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 37 publications
8
74
0
Order By: Relevance
“…6 However, the predictive value of noninducibility for VT recurrence is limited because ≤30% of patients who are rendered noninducible experience VT recurrences and more than half of the patients who remain inducible for nonclinical VTs do not present recurrence on short-term follow-up. 5 In line with prior recommendations, the majority of patients included in former studies of post-MI VT ablation had an advanced disease with poor left ventricular function, presenting with multiple VT episodes refractory to antiarrhythmic drugs (AAD), including amiodarone. [1][2][3][4][5]7 More recently, ablation early in the course of the arrhythmic disease has been recommended based on 2 randomized trials.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…6 However, the predictive value of noninducibility for VT recurrence is limited because ≤30% of patients who are rendered noninducible experience VT recurrences and more than half of the patients who remain inducible for nonclinical VTs do not present recurrence on short-term follow-up. 5 In line with prior recommendations, the majority of patients included in former studies of post-MI VT ablation had an advanced disease with poor left ventricular function, presenting with multiple VT episodes refractory to antiarrhythmic drugs (AAD), including amiodarone. [1][2][3][4][5]7 More recently, ablation early in the course of the arrhythmic disease has been recommended based on 2 randomized trials.…”
mentioning
confidence: 84%
“…5 In line with prior recommendations, the majority of patients included in former studies of post-MI VT ablation had an advanced disease with poor left ventricular function, presenting with multiple VT episodes refractory to antiarrhythmic drugs (AAD), including amiodarone. [1][2][3][4][5]7 More recently, ablation early in the course of the arrhythmic disease has been recommended based on 2 randomized trials. 8,9 Because of the reported high recurrence rates, despite noninducibility, new ablation end points like elimination of late or abnormal potentials have been suggested for all patients with scar-related VT, irrespective of baseline patient characteristics and clinical presentation.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Ablation techniques aiming at the elimination of the endocardial LPs and scar homogenization have been proven effective in treating VT. [3][4][5][6] Although the VT noninducibility after catheter ablation (CA) is commonly used as a procedural end point, some important limitations question the role of programmed ventricular stimulation (PVS) as a proof of long-term success after ablation. [7][8][9] We suggested that the LPs in SAECG correlate with the endocardial scar area and LPs in electro-anatomic maps of patients with ischemic cardiomyopathy. Further, we hypothesized that substrate-guided ablation and abolition of the endocardial LPs can result in normalization of the SAECG.…”
mentioning
confidence: 91%
“…[9][10][11] Patients who have VT rendered non-inducible by an ablation procedure have a lower VT recurrence rate and mortality compared with those who still have inducible arrhythmias after the ablation. 12 Catheter ablation has also been shown to be effective in the treatment of VT storm in patients with SHD receiving chronic AAD therapy. 13 In the setting of non-ischaemic SHD, catheter ablation outcome varies according to the nature of the underlying heart disease, with a greater need for epicardial mapping and ablation, higher recurrence rate and more AAD use in long-term follow-up.…”
mentioning
confidence: 99%